ERROR ANALYSIS OF USING RELATIVE PRONOUNS IN ADJECTIVE CLAUSE - Hermariyanti Kusumadewi (STKIP PGRI Lubuklinggau, 2019)
Relative Clause is a clause which uses relative pronoun to explain or describe more about the noun. The purpose of this research is to find out what type of errors that students make in forming adjective clause and what kind of relative pronouns which the students often make error. This research will be conducted qualitative method descriptively. The population for this research is the third semester students at English Education department academic year 2017/2018 at Indraprasta PGRI University. There are two classes which consist of 30 students for each, therefore the population of this research is 60 students. The technique of sample taking is random sampling. Therefore the researcher takes 20 students which is 30 percent of the population as a sample from the two classes randomly. To collect the data, the researcher uses three techniques: Observation, Test, and Library research. The study reveals that there are many students that do not understand how to use relative pronouns (who, whom, which, whose) correctly.